Hepatocellular carcinoma in intrathoracic ectopic liver tissue - Leiva, Alexis J.; Uliana, Julio A.; Bykaluk, Juan A.; Medori, Alfonso; Ferro, Alejandro M. (Revista Argentina de Cirugía, 2026)
Ectopic liver tissue is a rare finding due to aberrant migration of hepatic cells during embryonic development that is mostly found incidentally and has particular relevance because of its significant carcinogenic potential. Surgical management is usually indicated. We report the case of a 27-year-old female patient with thoracic back pain and a mass in the computed tomography scan who underwent surgery. A bibliographic review is also presented.